Implementasi Visi Misi Sekolah dalam Mewujudkan Siswa Berkarakter Religius di SMP Islam Terpadu Baitul Anshor Boarding School Cimahi - Usamah Almujahid; Asep Dudi Suhardini; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. Student delinquency that is occurs today is the background of this research. Bullying, drug abuse, promiscuity, brawls between students, and other student delinquency are examples of cases that often occur. The development of student behavior is related to the process of implementing activities in schools (Laure, et al., 2020). Therefore, this study looks at how the implementation of the school's vision and mission in realizing students with a religious character. This study aims to determine the planning carried out by the school, find out how the implementation of Islamic boarding school activities and find out how the evaluation is carried out on Islamic boarding school activities in implementing the vision and mission to realize students with a religious character.The research method used in this research is descriptive with survey methods and qualitative approaches. The types of data used are primary and secondary data. Sources of data were obtained from resource persons, namely the Head of School, Head of Islamic Boarding School, Deputy Head of Curriculum, Deputy Head of Student Affairs, Foster Brother, and Teachers. The data collection techniques used in this study were interviews, observations, and direct documentation at the Baitul Anshor Integrated Islamic Junior High School Cimahi.The results showed that by implementing the intracurricular and co-curricular programs in a sustainable and structured manner, the school's vision and mission could be implemented to realize students with religious character at the Baitul Anshor Integrated Islamic Junior High School Cimahi. Abstrak. Kenakalan remaja yang marak terjadi dewasa ini menjadi latar belakang penelitian ini. Bullying, penyalahgunaan narkoba, pergaulan bebas, tawuran antar pelajar, dan kenakalan remaja lainnya menjadi contoh kasus yang sering terjadi. Perkembangan perilaku siswa memiliki keterkaitan dengan proses pelaksanaan kegiatan di sekolah (Laure, et al., 2020). Oleh karena itu, pada penelitian ini melihat bagaimana implementasi visi dan misi sekolah dalam mewujudkan siswa berkarakter religius. Penelitian ini bertujuan untuk mengetahui perencanaan yang dilakukan oleh sekolah, mengetahui bagaimana pelaksanaan kegiatan kepesantrenan dan mengetahui bagaimana evaluasi yang dilakukan terhadap kegiatan kepesantrenan dalam mengimplementasikan visi dan misi untuk mewujudkan siswa berkarakter religius. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif dengan metode survei dan pendekatan kualitatif. Jenis data yang digunakan adalah data primer dan sekunder. Sumber data diperoleh dari narasumber yaitu Kepala Sekolah, Kepala Kepesantrenan, Wakil Kepala Bidang kurikulum, Wakil Kepala Bidang Kesiswaan, Kaka Asuh dan Guru. Adapun teknik pengumpulan data yang dilakukan dalam penelitian ini adalah wawancara, observasi, dan dokumentasi secara langsung di SMP Islam terpadu Baitul Anshor Boarding School Cimahi.Hasil penelitian menunjukkan bahwa dengan melaksanakan program intrakulikuler dan kokulikuler secara berkelanjutan dan terstruktur dapat mengimplementasikan visi dan misi sekolah untuk mewujudkan siswa berkarakter religius di SMP Islam terpadu Baitul Anshor Boarding School Cimahi.